SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A Modern Ghost Story: Increased Selective Mortality of Salmon Under Climate Extremes - Anna M. Sturrock; Kirsten Sellheim; Joseph Merz; Jamie Sweeney; Miranda Bell‐Tilcock; George Whitman; Kohma Arai; Malte Willmes; Carson Jeffres; Rachel C. Johnson (Global Change Biology, 2026)
Hydroclimate volatility poses a growing threat to species' persistence, particularly when combined with widespread habitat loss and other stressors. Although the negative impacts of drought on aquatic species are well documented, wet conditions are generally assumed to enhance recruitment of migratory species during freshwater life stages. Life‐history theory predicts that species with multiple migratory strategies should be more resilient to climate extremes by spreading risk across time and space. Testing these assumptions requires tracking both survivors and ‘ghosts’ across life stages and broad spatial scales. For many Pacific salmonids, a substantial fraction of the population disperses downstream soon after emergence (‘early migrants’), rearing in downstream habitats before entering the ocean. The extent to which hydroclimatic conditions influence selection against this phenotype and its lifetime success is poorly understood. To address this data gap, we tracked nine cohorts of Chinook salmon ( Oncorhynchus tshawytscha ) at sequential points through their life cycle, using otolith and eye lens isotopes to identify habitats and conditions associated with the highest losses of early migrants. Comparisons of juvenile ( n = 2197) and adult ( n = 3937) samples revealed large spatiotemporal variation in the strength of selective mortality. Early migrants became progressively rarer at each consecutive sampling point, including among adult returns, indicating carryover effects from freshwater into the ocean. At the southern edge of the species range—where water scarcity is an intensifying issue—we had predicted positive relationships between river flow, growth and survival. Instead, trends were consistently quadratic, suggesting that both drought and extreme high flows can reduce rearing opportunities and cohort strength. Ultimately, all phenotypes contributed to reproduction in all years, underscoring the importance of maintaining diverse life history portfolios and implementing climate‐ready restoration strategies that provide refugia and growth opportunities across the full spectrum of flow conditions.

Life Cycle Model Demonstrates Life-History Diversity Value and Recovery Options for a Reduced Pacific Salmonid Population at the Southern Extent of Its Range - Kai Ross; Joseph Merz (Environmental Modeling & Assessment, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Diversity in Habitat Use by White Sturgeon Revealed Using Fin Ray Geochemistry - Kirsten Sellheim; Malte Willmes; Levi S. Lewis; Jamie Sweeney; Joseph Merz; James A. Hobbs (Frontiers in Marine Science, 2022)
Understanding life-history diversity in a population is imperative to developing effective fisheries management and conservation practices, particularly in degraded environments with high environmental variability. Here, we examined variation in habitat use and migration patterns of White Sturgeon ( Acipenser transmontanus ), a long-lived migratory fish that is native to the San Francisco Estuary, CA, United States. Annual increment profiles were combined with respective geochemical ( 87 Sr/ 86 Sr) profiles in sturgeon fin rays to reconstruct annual salinity chronologies for 112 individuals from 5 to 30 years old. Results indicated a complex and diverse amphidromous life history across individuals, characterized largely by estuarine residence, a general ontogenetic trend toward higher-salinity brackish habitats, and high variability in habitat use across all age groups. Hierarchical clustering based on fin ray geochemistry during the first 10 years of life, prior to sexual maturation, indicated at least four distinct migratory phenotypes which differed largely in the timing and duration of juvenile to subadult movements between fresh- and brackish-water habitats. This study provides information regarding habitat use and migration in sub-adult fish that was previously lacking. Different migratory phenotypes vary in exposure to stressors across time and space and populations. Understanding White Sturgeon habitat distributions through space and time at different life stages can help identify areas where habitat restoration would be most effective and develop management actions to reduce stressors associated with specific areas where White Sturgeon are present.

Shade affects magnitude and tactics of juvenile Chinook salmon antipredator behavior in the migration corridor - Megan C. Sabal; Michelle L. Workman; Joseph E. Merz; Eric P. Palkovacs (Oecologia, 2021)
Environmental conditions strongly affect antipredator behaviors; however, it is less known how migrating prey adjust antipredator behavior in migration corridors, in part, because active migrants are difficult to observe and study. Migrants are vulnerable and encounter many predators in the corridor, and their propensity to travel towards their destination ties antipredator behavior with movement. We evaluated how environmental risk cues in the migration corridor including in-water habitat structure (present, absent) and overhead shade (sun, shade), and salmon origin (hatchery, wild) affected how juvenile Chinook salmon ( Oncorhynchus tshawytscha ) reacted to a live predator. We measured how salmon react to predation risk as the difference in time to swim downstream through a 9.1-m long field enclosure with or without a live predatory largemouth bass ( Micropterus salmoides ). Shade significantly modified the reaction to the predator, and it did so in two ways. First, the magnitude of antipredator behavior was larger in shade compared to direct sun, which suggests salmon perceived shade to be a riskier environment than sun. Second, the escape tactic also varied; salmon slowed down to be cautious in shade and sped up in sun. Structure did not significantly affect behavior and hatchery and wild salmon behaved similarly. Our study suggests that environmental risk cues can shape the magnitude and tactics of how migrants react to predation risk and illustrates how these responses relate to movement with potential to scale up and affect migration patterns.

Comparison of three sampling methods for small-bodied fish in lentic nearshore and open water habitats - Joseph E. Merz; Jesse T. Anderson; Jesse Wiesenfeld; Steven C. Zeug (Environmental Monitoring and Assessment, 2021)
We performed a preliminary evaluation of a mobile sampling platform with adjustable push net and live box (Platform) against two common methods for sampling small-bodied fish (i.e., 10–100 mm) in two distinct lentic habitats. Nearshore (NS) littoral habitat was sampled by Platform and beach seine, and open water (OW) pelagic habitat by Platform and Kodiak trawl. Our goal was to evaluate the Platform’s ability to describe fish assemblage structure across habitat types in contrast to common techniques restricted to single habitat types that are less comparable due to gear-specific bias. Platform sample speed had a significant positive effect on recapture efficiency of both nearly neutrally buoyant objects and marked fish. Marked fish recapture efficiencies were similar for Platform in NS and OW, indicating similar efficiency across habitat types. Platform capture efficiency was similar to beach seine and greater than Kodiak trawl. With similar sampling time, the Platform collected more individuals and taxa in NS relative to beach seine and in OW relative to Kodiak trawl. Greater taxa detection by the Platform suggests that it may be effective at detecting species that are numerically rare in specific habitats when compared to these methods. Fish CPUE was significantly greater NS regardless of technique. However, by using the Platform, there is greater confidence that this difference was reliable and not a gear selectivity artifact. Overall, this preliminary study demonstrates the Platform’s potential to collect standardized data across NS and OW habitats, track ontogenetic habitat shifts, and detect differences in small-bodied fish taxa richness, relative abundance, and density between NS and OW habitats. Continued experimentation beyond a single reservoir and fish size range is required before consensus can be established regarding the utility of this new push net design.

Ontogenetic patterns in the calcification and element incorporation in fin rays of age-0 White Sturgeon - Jamie K. Sweeney; Malte Willmes; Kirsten Sellheim; Levi S. Lewis; James A. Hobbs; Nann A. Fangue; Joseph E. Merz (Environmental Biology of Fishes, 2020)

Informed water management alternatives for an over‐allocated river: Incorporating salmon life stage effects into a decision tree process during drought - Kirsten Sellheim; Steven Zeug; Joseph Merz (Fisheries Management and Ecology, 2020)
Water competition in overallocated rivers is often extreme, and climate change exacerbates the challenge of balancing ecosystem and societal water needs. During a severe California drought in 2013–2014, storage in a strategic reservoir dropped to critically low levels, necessitating reduced downstream discharge during Chinook salmon, Oncorhynchus tshawytscha (Walbaum), incubation and rearing. In response, stakeholders developed an adaptive management process to balance competing water needs, including reservoir storage and salmon survival. This approach incorporated decision tree models, integrating salmon life stage transitions to define potential impacts. Life stage‐specific thresholds were identified and monitored to determine management triggers and actions. Flow reduction stranded up to 12% of incubating embryos and thus was used to trigger a flow pulse. Frequency of stranded fry in redds was reduced post‐pulse. Water quality did not change but remained within the species’ tolerance. High densities, poor body condition and aggressive behaviour of stranded fry triggered a second pulse three weeks later. This pulse reduced stranding and initiated downstream migration. Prescribed flow pulses supported outmigration of a keystone species while minimising water use during a critical period. This study evaluated ecological responses to management actions intended to ameliorate stressful low flow conditions and provided a decision‐making framework that can be used when resource use conflicts arise again.

Spatial variation of juvenile Chinook Salmon (Oncorhynchus tshawytscha) survival in a modified California river - Steven C. Zeug; Kirsten Sellheim; Jenny Melgo; Joseph E. Merz (Environmental Biology of Fishes, 2020)

Unnatural selection of salmon life histories in a modified riverscape - Anna M. Sturrock; Stephanie M. Carlson; John D. Wikert; Tim Heyne; Sébastien Nusslé; Joseph E. Merz; Hugh J. W. Sturrock; Rachel C. Johnson (Global Change Biology, 2020)
Altered river flows and fragmented habitats often simplify riverine communities and favor non‐native fishes, but their influence on life‐history expression and survival is less clear. Here, we quantified the expression and ultimate success of diverse salmon emigration behaviors in an anthropogenically altered California river system. We analyzed two decades of Chinook salmon monitoring data to explore the influence of regulated flows on juvenile emigration phenology, abundance, and recruitment. We then followed seven cohorts into adulthood using otolith (ear stone) chemical archives to identify patterns in time‐ and size‐selective mortality along the migratory corridor. Suppressed winter flow cues were associated with delayed emigration timing, particularly in warm, dry years, which was also when selection against late migrants was the most extreme. Lower, less variable flows were also associated with reduced juvenile and adult production, highlighting the importance of streamflow for cohort success in these southernmost populations. While most juveniles emigrated from the natal stream as fry or smolts, the survivors were dominated by the rare few that left at intermediate sizes and times, coinciding with managed flows released before extreme summer temperatures. The consistent selection against early (small) and late (large) migrants counters prevailing ecological theory that predicts different traits to be favored under varying environmental conditions. Yet, even with this weakened portfolio, maintaining a broad distribution in migration traits still increased adult production and reduced variance. In years exhibiting large fry pulses, even marginal increases in their survival would have significantly boosted recruitment. However, management actions favoring any single phenotype could have negative evolutionary and demographic consequences, potentially reducing adaptability and population stability. To recover fish populations and support viable fisheries in a warming and increasingly unpredictable climate, coordinating flow and habitat management within and among watersheds will be critical to balance trait optimization versus diversification.

Tissue Contaminant Burdens in San Francisco Estuary White Sturgeon (Acipenser transmontanus): Implications for Population Recovery - Deke T. Gundersen; Steven C. Zeug; Robert B. Bringolf; Joseph Merz; Zachary Jackson; Molly A. H. Webb (Archives of Environmental Contamination and Toxicology, 2017)

Long-Term Seasonal Trends in the Prey Community of Delta Smelt (Hypomesus transpacificus) Within the Sacramento-San Joaquin Delta, California - Joseph E. Merz; Paul S. Bergman; Joseph L. Simonis; David Delaney; James Pierson; Paul Anders (Estuaries and Coasts, 2016)

A conservation plan for Atlantic salmon ( Salmo salar ) and anadromous brown trout ( Salmo trutta ) in a region with intensive industrial use of aquatic habitats, the Hardangerfjord, western Norway - Øystein Skaala; Geir Helge Johnsen; Håvard Lo; Reidar Borgstrøm; Vidar Wennevik; Michael Møller Hansen; Joseph E. Merz; Kevin A. Glover; Bjørn T. Barlaup (Marine Biology Research, 2014)

Effects of predator and flow manipulation on Chinook salmon (Oncorhynchus tshawytscha) survival in an imperiled estuary - Bradley Cavallo; Joseph Merz; Jose Setka (Environmental Biology of Fishes, 2013)

Migration characteristics of hatchery and natural-origin Oncorhynchus mykiss from the lower Mokelumne River, California - S. Casey Del Real; Michelle Workman; Joseph Merz (Environmental Biology of Fishes, 2012)

Movement of Sacramento Sucker, Catostomus occidentalis, and Hitch, Lavinia exilicauda, during a Spring Release of Water from Camanche Dam in the Mokelumne River, California - Carson A. Jeffres; A. Peter Klimley; Joseph E. Merz; Joseph J. Cech (Environmental Biology of Fishes, 2006)